Designing new biocompatible glass‐forming Ti75‐xZr10NbxSi15 (x = 0, 15) alloys: corrosion, passivity, and apatite formation. Issue 1 (21st January 2015) - Abdi, Somayeh; Oswald, Steffen; Gostin, Petre Flaviu; Helth, Arne; Sort, Jordi; Baró, Maria Dolors; Calin, Mariana; Schultz, Ludwig; Eckert, Jürgen; Gebert, Annett
Abstract: Glass‐forming Ti‐based alloys are considered as potential new materials for implant applications. Ti75 Zr10 Si15 and Ti60 Zr10 Nb15 Si15 alloys (free of cytotoxic elements) can be produced as melt‐spun ribbons with glassy matrix and embedded single β‐type nanocrystals. The corrosion and passivation behavior of these alloys in their homogenized melt‐spun states have been investigated in Ringer solution at 37°C in comparison to their cast multiphase crystalline counterparts and to cp‐Ti and β‐type Ti‐40Nb. All tested materials showed very low corrosion rates as expressed in corrosion current densities i corr  < 50 nA/cm 2 . Electrochemical and surface analytical studies revealed a high stability of the new alloys passive states in a wide potential range. This corresponds to low passive current densities i pass  = 2 ± 1 µA/cm 2 based on the growth of oxide films with thickness d <10 nm. A homogeneous constituent distribution in the melt‐spun alloys is beneficial for stable surface passivity. The addition of Nb does not only improve the glass‐forming ability and the mechanical properties but also supports a high pitting resistance even at extreme anodic polarization up to 4V versus SCE were oxide thickness values of d ∼35 nm are reached. With regard to the corrosion properties, the Nb‐containing nearly single‐phase glassy alloy can compete with the β‐type Ti‐40Nb alloy. SBF tests confirmed the ability for formation of hydroxyapatite on the melt‐spun alloy surfaces. All these properties recommend the new glass‐forming alloys for application as wear‐ and corrosion‐resistant coating materials for implants. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 27–38, 2016.